PERLINDUNGAN HAK KEPERDATAAN TERHADAP ANAK AKIBAT PEMBATALAN PERKAWINAN SETELAH SALAH SATU PIHAK MENINGGAL - Syafiqa Tiara Ayunda; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The issue of canceling a marriage might be not that common in Indonesia Citizens. But cases like this are already common in big cities. The cancellation of the marriage is due to the non-fulfillment of the conditions of the marriage or violation of the marriage ban which is written in Law Number 1 of 1974 concerning Marriage by person who do not consider marriage as a sacred thing that must be met in order to be legal and sacred. Cancellation of marriage itself can be detrimental to various parties in the future.The purpose of this study is to determine the legal consequences of a marriage cancellation in which one party dies and the fulfillment of children's rights as a result of a marriage cancellation after one of the parties dies. This type of research is normative legal research or what is known as "legal research". In this normative study addressed the approach to the law. The law approach is carried out by examining all laws and regulations relating to the legal issues being addressed. Legal research with a law approach will examine the principles of law, examine the fulfillment of children's rights in a marriage that is annulled which is linked to the study of the theory of justice.In the results of research and discussion there are 2 main problems that can be concluded. First, The legal consequences of a marriage annulment in which one of the parties died do not apply retroactively to the child born in the marriage. However, if the child is born after a marriage is canceled, recognition and proof is needed for the child to get inheritance rights. Second, children who are illegitimate in the eyes of the state but legitimate in the eyes of religion are still entitled to the inheritance rights left by the father. However, a child whose position is illegitimate in the eyes of the state or religion is only entitled to the inheritance on his mother's side. For the fulfillment of a living can be discussed by the previous family of the father.Keyword: Legal Protection, Child’s Right, Marriage Cancellation